RETROSPECTIVE ANALYSIS OF INFRA ORBITAL NERVE INJURY IN FACIAL FRACTURES AT TERTIARY CENTRE OF GUJARAT - Shah, Rishabh; Agrawa, Pratik; Arora, Sonal; Shah, Parth; Shah, Navin; Shah, Navin (International Journal of Psychosocial Rehabilitation, 2020)
INTRODUCTION: Facial fractures are distributed in a fairly normal curve by age, with a peak incidence occurring between ages 20 and 40, and children under 12 suffering only 5–10% of all facial fractures. From amongst the facial fractures, Midfacial fractures account for a substantial proportion of maxillofacial injuries, predominantly presenting in young (20 to 40 year old) male patients. In the ZMC region the most common nerve to be involved is the infraorbital nerve injury METHOD: A retrospective analysis was done from the data gathered from the Medical records of Department of Oral & Maxillofacial Surgery of our tertiary care centre for the patients who were diagnosed with Midfacial, Pan facial and le-fort fractures, as the fractures of this type usually involves the infraorbital nerve injury which innervates (sensory) the lower eyelid, upper lip, and part of the nasal vestibule. The neurosensory changes were evaluated with the help of two point discrimination method. The data obtained were statistically analyzed after thorough preliminary inspection and content analysis and results and observation and a conclusion was drawn from it. RESULT: Males have shown to be the most commonly affected gender than females. Also it showed that out of 102 patients 33, of them had sustained infraorbital nerve injury which caused neurosensory disturbances to the areas that it supplied CONCLUSION : It was concluded that infraorbital nerve recover usually recovers within a span of 6 months if treated by open reduction and internal fixation surgery especially for the patients who are diagnosed with paresthesia of the Midfacial region